2008
DOI: 10.1016/j.jtcvs.2007.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Additive protection against lung ischemia-reperfusion injury by adenosine A2A receptor activation before procurement and during reperfusion

Abstract: Adenosine A2A receptor activation with ATL-313 results in the greatest protection against lung ischemia-reperfusion injury when given before ischemia and during reperfusion. Improved pulmonary function observed with adenosine A2A receptor activation was correlated with decreased bronchoalveolar lavage tumor necrosis factor alpha and decreased lung myeloperoxidase. The loss of protection observed with the concurrent administration of the adenosine A2A receptor antagonist, ZM 241385, supports that the mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 30 publications
(37 reference statements)
3
58
1
Order By: Relevance
“…Ischemia-reperfusion lung injury was attenuated by ATP-MgCl 2 in rats, although its effect was in part mediated by its breakdown product, adenosine, via A 2 receptors, probably on leukocytes, acting to prevent the production of damaging O 2 -derived free radicals (Hsu et al, 1994;Hirata et al, 2001;Chen et al, 2003). A 2A receptor agonists attenuated cardiac dysfunction arising from pulmonary ischemia-reperfusion injury (Reece et al, 2005;Ellman et al, 2008;Gazoni et al, 2008;Sharma et al, 2009). It has been claimed that A 2B receptors play a role in mediating lung inflammation after ischemia-reperfusion by stimulating cytokine production and neutrophil chemotaxis (Anvari et al, 2010).…”
Section: Ischemiamentioning
confidence: 99%
“…Ischemia-reperfusion lung injury was attenuated by ATP-MgCl 2 in rats, although its effect was in part mediated by its breakdown product, adenosine, via A 2 receptors, probably on leukocytes, acting to prevent the production of damaging O 2 -derived free radicals (Hsu et al, 1994;Hirata et al, 2001;Chen et al, 2003). A 2A receptor agonists attenuated cardiac dysfunction arising from pulmonary ischemia-reperfusion injury (Reece et al, 2005;Ellman et al, 2008;Gazoni et al, 2008;Sharma et al, 2009). It has been claimed that A 2B receptors play a role in mediating lung inflammation after ischemia-reperfusion by stimulating cytokine production and neutrophil chemotaxis (Anvari et al, 2010).…”
Section: Ischemiamentioning
confidence: 99%
“…We have previously demonstrated that A 2A R agonism significantly attenuates lung IR injury (23,33,34) and have defined a pivotal role of iNKT cell-produced IL-17 in the initiation of lung injury and inflammation after IR (3). A 2A R is the predominant adenosine receptor on iNKT cells (35).…”
Section: Original Articlementioning
confidence: 99%
“…All subtype classes of this receptor (A 1 , A 2A , A 2B and A 3 ) are expressed in lung tissue and work through adenyl cyclase or phospholipase C activation. Some studies attribute an anti-inflammatory role to A 1 , A 2A and A 3 (81) with reduction in oxidative stress by decreasing neutrophil-mediated O 2…”
Section: Adenosine A2a Receptor Agonistsmentioning
confidence: 99%